2014
DOI: 10.1373/clinchem.2014.221531
|View full text |Cite
|
Sign up to set email alerts
|

Harmonization of Measurement Results of the Alcohol Biomarker Carbohydrate-Deficient Transferrin by Use of the Toolbox of Technical Procedures of the International Consortium for Harmonization of Clinical Laboratory Results

Abstract: BACKGROUND:The need for equivalent results of routine measurement procedures for the alcohol biomarker carbohydrate-deficient transferrin (CDT) has been recognized by the IFCC. This article describes a project to harmonize CDT as conducted by an IFCC working group initiated for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 21 publications
2
21
0
Order By: Relevance
“…However, the harmonization procedure recently proposed by IFCC-WG-CDT across CDT routine measurement procedures [26] should reduce the bias between the two methods and improve CDT reporting.…”
Section: Discussionmentioning
confidence: 99%
“…However, the harmonization procedure recently proposed by IFCC-WG-CDT across CDT routine measurement procedures [26] should reduce the bias between the two methods and improve CDT reporting.…”
Section: Discussionmentioning
confidence: 99%
“…Harmonization of the assay obviously is important. The Calibration 2.000 project and co-workers of it contributed both to harmonization [64,65] and to the development of a reference method [63].…”
Section: Endocrinology Binding Assays Vitaminsmentioning
confidence: 99%
“…Weykamp et al recently reported on their efforts toward the harmonization of carbohydrate-deficient transferrin (CDT) measurements in serum (1 ). Alcohol biomarkers play a key role in the identification of alcohol abuse, a chronic disorder with enormous health and legal implications.…”
Section: Combining Serum Carbohydrate-deficient Transferrin and Hair mentioning
confidence: 99%